Recursos digitales en el aprendizaje cooperativo en estudiantes de décimo año de EGB, Unidad Educativa Babahoyo - Estrada Hernandez, Hugo Ramón (2023)
In the present research project whose topic is digital resources in cooperative learning in tenth year students of Basic General Education, in the Educational Unit Babahoyo, which aims to determine the contribution of digital resources in cooperative learning, for which the research of Exploratory, Descriptive and Explanatory Research were applied. There was a population of twelve teachers who teach in different parallels along with one hundred and fifty one students, the measurement instruments that were implemented to obtain the data were the questionnaire. In the research work we deal with topics such as, which are the digital resources, the types of digital resources, also mentioned are some that have few implemented such as Discord, Parsec, and eXeLearning, with regard to cooperative learning a small explanation is given about what cooperative learning is, its characteristics along with its advantages and disadvantages for both variables.